Urbanization in Northern Corridor Economic Region in Malaysia - Yusoff, Noraniza (IntechOpen, 2019)
Urbanization in Northern Corridor Economic Region in Malaysia presents five chapters: Introduction, Paradigm of Urbanization, The Rise of Urbanization, Urbanization in Northern Corridor Economic Region, and Strategy on Urbanization. The book provides an insight into scientific literature on the topic of urbanization, encompassing a variety of publications such as books, magazines, journals, and other formats. The notion of urbanization, related to the urban model and theory, is becoming recognized in academic spheres. Urban theory, within the urban context, aims to define objectives and distinct approaches for the common realization of city living. Urban transition consists of a variety of elements that transform the urban region. The data presented in the book examines the link between various perspectives on urbanization and their outcomes. The strategies on urbanization must involve many domains, because an estimated 1.6 billion citizens currently reside in urban regions.